The Effectiveness of Hypnoteaching Method in Improving Students Mandarin Learning Activities at the Dharma Bunda Kasih Indonesia Foundation - Darwin, David; Boeriswati, Endry; Setiadi, Samsi (KnE Social Sciences, 2024)
In the learning process, teacher as an educator is required to design and implement specific teaching methods to improve learning outcomes. This research aims to assess the effectiveness of implementing the hypnoteaching method in enhancing Mandarin language learning activities for students at the Dharma Bunda Kasih Indonesia Foundation. The research method employed is a combination of sequential exploratory methods characterized by its research focus. The findings indicate that the hypnoteaching method can be used by teachers to create an effective and enjoyable learning environment. The effectiveness of this teaching method is demonstrated by the results of the semester II exams in the XI grade at the Dharma Bunda Kasih Indonesia Foundation, where the average score of all students was 87. Additionally, it was known from the average score that students’ absorption of learning material was 87%. The calculations shows that the average student scores fall within the 86-100 range in the conversion of learning effectiveness, categorized as ’Very Effective.’ Therefore, the data on student learning outcome calculations indicate that the implementation of the hypnoteaching teaching method is effective in improving students’ learning activities. Based on T-test analysis, it can be concluded that learning with the hypnoteaching method yields better results compared to direct learning. Keywords: hypnoteaching, learning activities, Mandarin